Awareness in action : the role of consciousness in language acquisition - Szczesniak, Konrad; Lyda, Andrzej (Second Language Learning and Teaching,, 2014)
The papers included in the volume look at how language awareness affects the outcomes of foreign and second language acquisition in advanced learners. The  book focuses on questions such as how much linguistic knowledge is open to the learner's conscious experience, what should and should not be considered the knowledge of language, how language awareness can be enhanced in the classroom, and, most crucially, what effects language awareness has on attained proficiency. Some papers in the volume also address methodological challenges of researching language awareness, such as the difficulty of defining and measuring awareness with sufficient precision.